Photovoltaic array for powering advanced oxidation processes: Sizing, application and investment costs for the degradation of a mixture of anthracene and benzo[a]pyrene in natural water by the UV/H2O2 system (2018)
Advanced oxidation processes (AOPs) are commonly known as efficient water treatment techniques able to oxidize a great variety of pollutants from water that are otherwise difficult to be converted. Nevertheless, AOPs are costly processes, particularly, because of the electrical costs associated. In this regard, photovoltaic (PV) energy can be used to power the AOP in a reliable and autonomous way. In this work, the steps for sizing a solar PV system for water treatment using AOPs are described. Additionally, the feasibility of the use of a PV array without batteries to supply the electrical power needs of a UV/H2O2 advanced oxidation system for degrading natural water containing 12 and 3 μg L−1 of anthracene and benzo[a]pyrene, respectively, two of the priority polycyclic aromatic hydrocarbons because of their harmful effects on living beings, was studied. It was found that more than 99% of anthracene and benzo[a]pyrene were removed and about 45% of the total organic matter was mineralized after 15 and 90 min of treatment, indicating the high efficiency of the system. Finally, the investment costs of the UV/H2O2-PV system for a small application were estimated with and without batteries in order to define the optimum PV array configuration. The PV array designed and applied allows for the decontamination of persistent pollutants in natural water in an environmentally-friendly and sustainable way.